PATHOGENETIC ASPECTS OF THE HIPPOCAMPUS AFFECTION UNDER THE EXPERIMENTAL CARDIOMYOPATHY - Кozlova Yu.V.; Kozlov, S.V.; Rodynskyi, O.G.; Koldunov, V.V.; Kosharnyi, V.V.; Abdul-Ohly, L.V.; Rodynska, G.O. (World of Medicine and Biology, 2018)
The article is devoted to the current problem of the present day: changes in the psycho-emotional sphere of patients with a cardiac activity disorder. Moreover, clinical observations point out to a wide range of cognitive activity disorders in various mechanisms of heart damage at different stages of the disease. Previous experimental studies have shown that the main link in the pathogenesis of cognitive impairment in the course of cardiomyopathy (CMP) is the change in blood supply to the brain, resulting in circulatory hypoxia. Other researchers attribute behavioral and cognitive disorders to the anatomical and functional features of the brain, namely the hippocampus. Thus, deepening of the existing data on behavioral and cognitive impairments and pathomorphological changes of the hippocampus in the dynamics of the experimental CMP development, will permit not only to establish the presence of changes, but also to identify new pathogenesis links. This will facilitate the development of new therapeutic measures and, most importantly, algorithms for the prevention of cognitive dysfunctions. Therefore, the purpose of the study was establishing the pathogenetic connection of behavioral and cognitive disorders with morphological changes of the hippocampus in dynamics in modeling of experimental cardiomyopathy. In order to achieve the assigned goal, 259 Vistar white male rats aged 5-7 months, weighing 180-220 g, were divided into 2 groups: group I (control): 0.9% NaCl solution (n = 130) and group II (experimental): five times doxorubicin was administered in a dose of 5.0 mg / kg of the mass intraperitoneally at intervals of 1 week (n = 129). All studies with laboratory animals were carried out in compliance with modern bioethical standards. The behavior of rats was studied in the "Open Field" test, and the cognitive function was estimated based on the results of the passive avoidance conditional response test. Pathomorphological and immunohistochemical studies as well as the spectral study of the hippocampus were performed according to standard techniques. Applying the above methods, the dynamics (1; 3; 7; 14; 21 and 28 days) of CMP development was traced in behavioral and cognitive changes in rats, which well manifest CNS disorders, including the hippocampus. The analysis of Fisher’s (F) criterion change has shown that CMP mostly affected the orientational and exploratory activity of the experimental rats, namely, the horizontal motor activity and the exploration of the openings. The analysis of the obtained spectrometry results showed that the content of Fe, Na, Ca and P in the CMP rats was reliably reducing by 54%, 51%, 56.5% and 40%, respectively. At the same time, the concentration of K, Mg and Cu reliably increased by 13.5%, 11% and 6% respectively. In the CMP rats, a distinct difference in the density of neurons was detected separately between different fields of the hippocampus and was rapidly reducing in all fields of the hippocampus. As a result of the performed immunohistochemical study, a positive response was observed with the immunohistochemical Ki-67 proliferation marker (Fig. 3): mostly in endothelial cells in both large vessels and capillaries, as well as in the sections of the brain in the polymorphic layer of the hypocampus, there were occasional immune-positive glyocytes (expression of the proliferative marker outside the hippocampus being more saturated). The results obtained primarily indicate a significant brain damage, particularly the hippocampus, in the dynamics of the experimental CMP development. A significant reduction in neurons, a slight expression of the caspasa-3 apoptotic marker, and the absence of an inflammatory response indicate to the nerve cells death through apoptosis. All of the above changes are evidently the result of circulatory hypoxia in the background of the experimental CMP.